STRATEGI INDUCTIVE LEARNING PADA PEMBELAJARAN ENGLISH GRAMMAR UNTUK MENINGKATKAN KOMPETENSI GRAMATIKAL MAHASISWA - Galuh Kirana Dwi Areni; Intan Permata Hapsari; Novia Trisanti (Jurnal Penelitian Pendidikan, 2013)
This study focuses on a class action research (CAR) which tried to apply a method of Inductive Learning in a class of Advanced English Grammar to improve the students’ grammatical competence and to find out whether there were students’ behaviour changes in learning English grammar. This class action research (CAR) was conducted in two cycles. In each cycle, there were four steps, i.e planning, acting, observing, and reflection. Every cycle was conducted in two class meetings. The material for cycle 1 was ‘the position of adjectives’ and the material for cycle 2 was ‘the forms of adjectives.’ The subjects of the study were the 4 semester students of an Advanced English Grammar class in academic year 2011/2012. These students were Literature Study Program students of English Department Unnes. Based on the data analysis, the result of this CAR was quiet satisfying. There was an increasing percentage of students’ test scores between cycle 1 and cycle 2. From test cycle 1, there were 32% students who got less than 70, while this reduced to only 24% students in test cycle 2. In addition, there were 68% students who got 71-100 in test cycle 1 and it increased to 76% students in test cycle 2. Based on the observation sheets and questioners given to the students, most of them liked Inductive Learning method to be applied in grammar classes because this method is fun and interesting. This attitude directly influenced their activity, motivation, and behavior in grammar classes which indirectly also increased their grammatical competence. Finally, the pedagogical implication th of the study is the lecturers and students are supposed to fully motivated to use Inductive Learning method in their grammar classes. This method, hopefully, can improve students’ activity, motivation, behavior, and grammatical competence in learning English grammar.